The role of the nurse in the care of a post-operative cesarean patient with HELLP syndrome in the gynecology and obstetrics service of a National Hospital, 2022 - Carlos Eva , Gutiérrez; Castro Paucar, Eguiluz (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Pregnancy with hellp syndrome is life-threatening, it appears in 5-9 out of every 1000 pregnancies and in 10-20% of cases with severe preeclampsia, it causes the breakdown of red blood cells, causing liver problems , bleeding and blood pressure. The objective of this study is to manage nursing care for a patient with síndrome of hellp and hemoperitoneum with pelvic hematoma in the obstetrics-gynecology service. The present study is a research with a qualitative approach, clinical case type, study subject female, 21 years old. The nursing care process was used as a method, the assessment guide of Marjorie Gordon's 11 functional patterns was applied, by which altered patterns were found, formulating the nursing diagnoses: Decreased cardiac output, Acute Pain and CP: Shock hypovolemic. The activities were executed in a timely manner, the evaluation was through the difference in baseline and final scores of the indicators. We can conclude that hellp syndrome is a hypertensive disorder of pregnancy, however, the complication of this post-cesarean patient is hemoperitoneum with pelvic hematoma, timely nursing care against this was the main axis in the patient's restoration. It is concluded that, according to the problems identified in the patient, the nursing care process was managed in its five stages, improving the patient's health status, but the survival and success of the treatment provided depends on the timely identification of the problems and appropriate choice of treatment